CONSTRUCTION AND EVALUATION OF MALL-BASED LEARNING MATERIALS WITH THE INTEGRATION OF BUSINESS CASE STUDIES TO ENHANCE ENGLISH READING COMPREHENSION FOR MANAGEMENT STUDENTS. - Tiana, Ella Aprilia; Maruf, Nirwanto (University of Kuningan, 2024)
The purpose of this study was to develop and assess MALL (Mobile-Assisted Language Learning)-based learning materials, integrated with business case studies, to enhance English reading comprehension among management students. The research aimed to address the specific language needs of these students in the business context. Employing a mixed-methods design, the study used Pre-test and Post-test Assessments for quantitative analysis and Semi-structured interviews for qualitative insights. Results showed a statistically significant improvement in reading comprehension, with a t-value of 8.45 and a p-value of less than 0.001, indicating that the improvement was a direct effect of the MALL-based intervention. The Cohen’s d effect size was 1.2, suggesting a strong impact on students' reading comprehension skills. Qualitative data revealed increased engagement and motivation due to the interactive features of the MALL applications, and the relevance of the reading materials to future professional roles. However, usability challenges, such as navigation difficulties and application performance issues, were also noted. These challenges indicate a need for further refinement of the application design. Overall, integrating business case studies into MALL-based materials significantly enhances English reading comprehension for management students, with implications for curriculum development and instructional design in specialized language education contexts.